The development and validation of a quality of life measure for the carers of people with Parkinson's disease (the PDQ-Carer) - Jenkinson, C; Dummett, S; Kelly, L; Peters, M; Dawson, J; Morley, D; Fitzpatrick, R (2012)
Background: Parkinson's disease (PD) can have substantial effects not only on the quality of life of those diagnosedwith the condition but also upon the informal carers who provide support and assistance to them. However, to date no well-validated carer specific quality of life measure has been developed for carers of people with PD. Objective: This paper documents the development and validation of a PD specific carer quality of life scale. Methods: In depth interviews were undertaken with carers of people with PD. The interviews were transcribed and analysed thematically to derive a pool of potential items for the questionnaire. A pilot survey was used to refine the initial version of the questionnaire. A developmental survey was undertaken and the results analysed to produce the final 29-item measure. A validation survey was then undertaken to assess the construct validity and reliability of the measure. Results: Survey results suggest a 29-item questionnaire tapping four dimensions of quality of life (Social and Personal Activities, Anxiety and Depression, Self care, and Strain). Internal consistency reliability was found to be high for all domains. Data completeness was high. Construct validity (assessed by correlations with a generic measure of quality of life) confirmed prior hypotheses. Conclusion: The 29-item Parkinson Disease Questionnaire for Carers (PDQ-Carer) is a short, meaningful quality of life instrument, which taps areas of specific salience and concern to PD carers. © 2012.